Solar energy e-learning laboratory - Remote experimentation over the Internet - Economides, K.; Eleftheriou, Polyvios; Michaelides, Ioannis (My University, 2005)
This paper presents the solar energy e-learning laboratory, developed at the Higher Technical Institute (HTI) within the framework of the Leonardo da Vinci project MARVEL, focuses on the system architecture and its features, and elaborates on the learning platform employed. The laboratory focuses on experiential based learning-arrangements allowing remote and distributed training with the laboratory of solar energy. As a prototype working example the HTI solar energy laboratory comprises a remotely accessible pilot solar energy conversion plant employing the state of the art in software design.
Keywords: Remote engineering; Remote laboratory; Remote access; E-learning; Solar energy; Booking system; TestPoint; Moodle; Software architecture; Open access publishing